Identification of critical material thickness for eliminating back reflected shockwaves in laser shock peening – A numerical study. (October 2021) - Mylavarapu, Phani; Bhat, Chinmai; Perla, Manoj Kumar Reddy; Banerjee, Kumkum; Gopinath, K.; Jayakumar, T.
Graphical abstract: Highlights: Distorted residual stress profiles due to back reflected shock waves in laser peening. 2-D axisymmetric model for hitherto not defined critical material thickness determination. Computationally intensive kinetic energy plots identify critical thickness. In-depth shock wave pressure attenuation plots also identify critical thickness. Material thickness of minimum 2.5 times the laser spot diameter essential. Abstract: Laser Shock Peening (LSP) is one of the emerging surface treatment processes being considered for inducing beneficial compressive surface residual stresses in fatigue critical components. Owing to the ease in handling multiple parameters during optimization of process parameters, simulation based parameterization studies using finite element (FEM) based numerical models are widely gaining importance. Most of the LSP modeling performed so far considered infinite elements in both thickness and lateral directions. However, infinite elements in thickness direction would neglect the deleterious effect of shock wave back reflections for certain sample thicknesses. These back reflections have been reported to result in formation of subsurface cracks in the specimen. Therefore, in this study, using an alternative modeling strategy, effect of thickness on the back reflection of shock waves and its subsequent effect on residual stresses induced are discussed. A 2-D axi-symmetric model with infinite elements in lateral direction and finite elements in thickness direction is developed to simulate a single spot LSP process using ABAQUS/CAE FEM package. It is found that there exists a critical material thickness depending on spot diameter below which the effects of back reflection are predominant.